Evaluation of a new immunochromatographic assay for rapid identification of influenza A, B, and A(H1N1)2009 viruses - Mitamura, Keiko (Springer Japan, 2012)
We evaluated Clearline Influenza A/B/(H1N1)2009, a new multi-line immunochromatographic assay for rapid detection of antigens of influenza A (Flu A), B (Flu B), and A(H1N1)2009 viruses. Clearline detected Flu A, Flu B, and A(H1N1)2009 viruses with a detection limit of 4.6 × 10(3) to 7.5 × 10(4) pfu/assay. The sensitivity and specificity of detection of influenza virus by Clearline, using RT-PCR as reference standard, were determined for A(H1N1)2009, Flu A, and Flu B, in nasopharyngeal aspirate, nasopharyngeal swab, and self-blown nasal discharge specimens. Sensitivity for nasopharyngeal aspirate specimens was: A(H1N1)2009 = 97.3 %, Flu A = 94.5 %, and Flu B = 96.8 %, and specificity was Flu A = 99.1 % and Flu B = 100 %. Sensitivity for nasopharyngeal swab specimens was: A(H1N1)2009 = 91.9 %, Flu A = 92.8 %, and Flu B = 100 %, and specificity was Flu A = 98.2 % and Flu B = 100 %. Sensitivity for self-blown nasal discharge specimens was: A(H1N1)2009 = 75.7 %, Flu A = 86.5 %, and Flu B = 76.2 %, and specificity was Flu A = 98.4 % and Flu B = 100 %. Sensitivity and specificity of Clearline were sufficient for nasopharyngeal aspirate and swab specimens. For self-blown nasal discharge specimens, sensitivity was lower than for nasopharyngeal aspirates and nasopharyngeal swabs. The sensitivity of Clearline for A(H1N1)2009 was good even 6 h after the onset of symptoms. These findings suggest that Clearline may be useful for early clinical diagnosis of influenza.